2021
DOI: 10.1016/j.heliyon.2021.e06052
|View full text |Cite
|
Sign up to set email alerts
|

Gluten free rice-soy pasta: proximate composition, textural properties and sensory attributes

Abstract: Recent increase in gluten allergy has led to high demand for gluten free products such as rice pasta. Although rice grains are rich in bioactive compounds and B vitamins, they are generally low in protein compared to wheat grains. The aim of this study was to determine the quality attributes of soy enriched rice pasta. Five Rice-soy pastas were produced from different blends (10–30%) of soybean flour and rice flour. The proximate composition, cooking quality, colour, texture profile, and sensory attributes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 27 publications
4
13
0
1
Order By: Relevance
“…These flours have economic potential for both developing and developed countries and make a substantial nutritional contribution [ 19 ]. Common plant-based flours that have been used for the production of wheat flour-based products in different parts of the world include different legumes/pulses [ 29 , 30 , 31 , 32 , 33 ], different cereal crops [ 34 , 35 , 36 , 37 ] and some roots and tuber crops [ 38 , 39 , 40 , 41 ].…”
Section: Flourmentioning
confidence: 99%
See 1 more Smart Citation
“…These flours have economic potential for both developing and developed countries and make a substantial nutritional contribution [ 19 ]. Common plant-based flours that have been used for the production of wheat flour-based products in different parts of the world include different legumes/pulses [ 29 , 30 , 31 , 32 , 33 ], different cereal crops [ 34 , 35 , 36 , 37 ] and some roots and tuber crops [ 38 , 39 , 40 , 41 ].…”
Section: Flourmentioning
confidence: 99%
“…Soybean ( Glycine max ) has high lysine content and this makes it an ideal crop to improve the essential amino acids profile when blended with cereal crops. It has been used to produce bread [ 51 ], noodles [ 52 ] and pasta [ 33 ].…”
Section: Flourmentioning
confidence: 99%
“…Regarding health aspects, medical studies have shown that the consumption of lentils has benefits on cardiovascular diseases and cancer prevention [18], but also has implications in promoting slow and moderate postprandial blood glucose increase [19,20]. Soybean is boasted as having a significant amount of high-quality protein (38-55%), essential amino acids, lipids (20%), and carbohydrates (27%) [21][22][23]. The phytochemicals present in soybean are of great interest for health because studies have shown that they lower the amount of cholesterol, have an anticarcinogenic capacity, and contribute to bone health [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a similar decrease in hardness, particularly in pasta fortified with soybean, rice and tapioca flour. 64 This decrease is often associated with a weakening of the structure, which modifies the gluten-starch matrix due to the incorporation of plant powders. Texture cohesiveness indicates the ability of samples to hold together upon cooking and the ability to stick to itself, 65 while the springiness profile measures the degree of recovery after pasta compression.…”
Section: Tpa Of Pastamentioning
confidence: 99%